An Enzyme-Free DNA Circuit-Assisted Graphene Oxide Enhanced Fluorescence Anisotropy Assay for MicroRNA Detection with Improved Sensitivity and Selectivity - Zhen, Shu Jun; Xiao, Xue; Li, Chun Hong; Huang, Cheng Zhi (Analytical chemistry (Washington), 2017)
Graphene oxide (GO) has been proven as an outstanding fluorescence anisotropy (FA) amplifier. Yet the traditional GO amplified FA assays lack high sensitivity because of the 1:1 binding ratio between target and dye-modified probe. Herein, we report a new target-catalyzed hairpin assembly (CHA), an enzyme-free DNA circuit, assisted GO amplified FA strategy for microRNA-21 (miRNA-21) detection. In the presence of miRNA-21, the CHA was initiated and plenty of H1-H2 duplexes were produced continuously. The obtained H1-H2 duplex could induce the formation of a H1-H2-probe DNA (pDNA) complex by the toehold-mediated strand exchange reaction, which led the dye-modified pDNA to leave away from the GO surface, resulting in a decreased FA of the system. By monitoring the decrease of FA, miRNA-21 could be detected in the range of 0-16 nM. The limit of detection (LOD, 3σ) was 47 pM, which was 194 times lower than that without CHA. In addition, the selectivity of this method has also been enhanced greatly as compared to that without CHA. Our method has great potential to be applied for detecting different types of targets and monitoring diverse molecular interactions by adapting the corresponding nucleotide sequence.